Wage Premiums and Profit Maximization in Efficiency Wage Models. - MacLeod, W; Malcomson, J (1993)
The standard shirking model of efficiency wages is essentially a continuous-time, repeated prisoners' dilemma game. Thus, to sustain an equilibrium with employment requires sufficient gains from future cooperation. Each division of these gains corresponds to some equilibrium. Efficiency wages correspond to employees receiving the gains. Bonds allow firms to receive them. In markets well informed about agents' pasts, employment is independent of the distribution of gains. But in anonymous markets with more workers than jobs, employment is highest in efficiency wage equilibria. Efficiency wages, thus, arise naturally as the unique efficient equilibrium without recourse to assumptions that limit bonding.